2018
DOI: 10.1021/acs.est.8b00408
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple Pathways to Bacterial Load Reduction by Stormwater Best Management Practices: Trade-Offs in Performance, Volume, and Treated Area

Abstract: Stormwater best management practices (BMPs) are implemented to reduce microbial pollution in runoff, but their removal efficiencies differ. Enhanced BMPs, such as those with media amendments, can increase removal of fecal indicator bacteria (FIB) in runoff from 0.25-log to above 3-log; however, their implications for watershed-scale management are poorly understood. In this work, a computational model was developed to simulate watershed-scale bacteria loading and BMP performance using the Ballona Creek Watersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Watershed-scale implementation of SCMs has been investigated regarding water quantity, but fewer studies have investigated the impacts of watershed-scale installation of SCMs on water quality, 102,103 and only two studies to date have looked at watershed scale effects of biochar-augmented biofilters. 104,105 Studies have generally found that installation of biofilters results in improved water quality at the watershed scale, but these results vary in extent depending on watershed size, climate, impervious area treated, and pollutants of concern. 102,103 For example, Bedan and Clausen 106 monitored a watershed in the US state of Connecticut and found SCM installation decreased storm flows, nitrogen, Pb, and Zn loads compared to a paired control watershed without SCMs, while total P and total suspended solids loads increased relative to the control watershed.…”
Section: Watershed Scale Implementation Of Biochar-augmented Biofiltersmentioning
confidence: 99%
See 2 more Smart Citations
“…Watershed-scale implementation of SCMs has been investigated regarding water quantity, but fewer studies have investigated the impacts of watershed-scale installation of SCMs on water quality, 102,103 and only two studies to date have looked at watershed scale effects of biochar-augmented biofilters. 104,105 Studies have generally found that installation of biofilters results in improved water quality at the watershed scale, but these results vary in extent depending on watershed size, climate, impervious area treated, and pollutants of concern. 102,103 For example, Bedan and Clausen 106 monitored a watershed in the US state of Connecticut and found SCM installation decreased storm flows, nitrogen, Pb, and Zn loads compared to a paired control watershed without SCMs, while total P and total suspended solids loads increased relative to the control watershed.…”
Section: Watershed Scale Implementation Of Biochar-augmented Biofiltersmentioning
confidence: 99%
“…108 Existing studies show pollutant reduction is often correlated to the hydrologic processes such as infiltration and volume reduction, and not necessarily the biogeochemical processes occurring within the filters. 102,104 Surface water quality is regulated at the watershed scale, and biofilters can be used to help reach compliance, but the extent of installation is often substantial and costly. For example, Gagrani et al 109 evaluated the efficacy of using backyard biofilters in conjunction with the existing SCM network to reach mandated pollutant load reductions of 85% for TSS and 70% for total P (in comparison to predevelopment conditions) for a watershed in the southeast United States.…”
Section: Watershed Scale Implementation Of Biochar-augmented Biofiltersmentioning
confidence: 99%
See 1 more Smart Citation
“…Vogel et al [48] discuss geomedia mixes and BMP design modifications to target specific pollutants; Wolfand et al [49] show geomedia can improve water quality compliance for load-and concentration-based standards.…”
Section: Design Advice From Interviews (I) and Authors (A) For In-strmentioning
confidence: 99%
“…The degradation of water quality and flooding problems could be mitigate by introduce a promising solution with the application of suitable stormwater Best Management Practices (BMPs) at the catchment [9]. This judgment of using Stormwater facilities/BMPs depends on not only relevant theoretical considerations but also a significant amount of practical experience and the availability of relevant data, as well [10]. Determining the nature and magnitude of a problem is a prerequisite to planning and development of cost-effective solutions [11].…”
Section: Introductionmentioning
confidence: 99%